1993
DOI: 10.1007/bf00685875
|View full text |Cite
|
Sign up to set email alerts
|

Phase I pharmacokinetics study of high-dose fotemustine and its metabolite 2-chloroethanol in patients with high-grade gliomas

Abstract: The pharmacokinetics of high-dose fotemustine followed by autologous bone-marrow transplantation during a phase I-II clinical trial in 24 patients with glioblastoma or astrocytoma (grade III-IV) was investigated. Plasma levels of fotemustine were determined by high-performance liquid chromatography (HPLC) and UV detection. The metabolite, 2-chloroethanol, was simultaneously followed in six patients by gag liquid chromatography and electron capture detection (GLC-ECD) assay. The drug was given as a 1-h infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Fotemustine concentration in the cerebrospinal fluid reached 23% of plasma level. Its excretion is mainly urinary and fecal excretion is minimal [4]. Regarding its adverse events, the most important toxic events are thrombocytopenia, leukopenia, and anemia, while liver and kidney toxicity are moderate [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fotemustine concentration in the cerebrospinal fluid reached 23% of plasma level. Its excretion is mainly urinary and fecal excretion is minimal [4]. Regarding its adverse events, the most important toxic events are thrombocytopenia, leukopenia, and anemia, while liver and kidney toxicity are moderate [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous retrospective and prospective phase II studies showed an important activity of fotemustine in recurrent glioblastoma [6, 7] with a range of median overall survival from start of fotemustine treatment from 6 months to 11 months [7, 8]. Fotemustine (diethyl 1-{1-[3-(2-chloroethyl)-3-nitrosoureido] ethyl} phosphonate) is an alkylating [9] cytotoxic agent, belonging to the group of nitrosourea. It is characterized by elevated lipophilic properties and a low molecular weight that contribute to facilitation of its passage through the blood-brain barrier [10].…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor activity of fotemustine is related to its ability to alkylate DNA. After intravenous infusion, the plasma concentration reached the steady state in 45 minutes and the plasma concentration varied between 1 and 14 ug/mL disappearing in the blood within three hours [9]. …”
Section: Introductionmentioning
confidence: 99%